2019
DOI: 10.1136/bjophthalmol-2019-314403
|View full text |Cite
|
Sign up to set email alerts
|

Local therapy for cancer therapy-associated uveitis: a case series and review of the literature

Abstract: Background/aimsImmunotherapy and targeted therapy for metastatic cancer may cause immune-related adverse events (irAEs) such as uveitis. If irAEs are severe or require systemic steroids, cancer therapy is often held or discontinued. Local steroid therapy for cancer therapy-associated uveitis allows the continuation of cancer therapy. This series demonstrates successful management of cancer therapy-associated uveitis with local therapy based on uveitis subtype.MethodsThis is an Institutional Review Board-approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…This can be challenging, because the ocular symptoms experienced may not directly correlate with the severity of inflammation identified. 14 Even so, in most of the case series published to date, the overwhelming majority of patients experiencing ocular irAEs have had their CPIs discontinued, 12,13 and uncertainty exists whether this line of action may impact overall treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This can be challenging, because the ocular symptoms experienced may not directly correlate with the severity of inflammation identified. 14 Even so, in most of the case series published to date, the overwhelming majority of patients experiencing ocular irAEs have had their CPIs discontinued, 12,13 and uncertainty exists whether this line of action may impact overall treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding trials that do not report lower grade adverse events to the routine adverse event database results in a higher end estimate of 242/3255 patients on study treatment arms reporting ocular adverse events (7.4% prevalence). Ocular events occurred early after drug initiation (routine database: median 6 weeks, IQR 0-16, serious adverse events database: median 11 weeks, IQR [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The median Common Terminology Criteria for Adverse Events grade was grade 1 (mild) (IQR 1-2) and grade 2 (moderate) (IQR 2-3) for the routine database and the serious adverse events database, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…3 PD-1/PD-L1 inhibitor-associated adverse events (AEs) in the eye are also known to occur, but are rare and therefore less wellstudied. Case reports, case series, safety analyses, and some observational studies have shown that these drugs can cause inflammatory eye disease, such as uveitis, [3][4][5][6][7][8][9] scleritis, 8 dry eye syndrome, 4 5 9 10 optic neuropathy 9 and orbital myopathy. 11 Additionally, ipilimumab, a cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) checkpoint inhibitor in a similar class as PD-1/PD-L1 inhibitors, has been documented to cause potentially blinding conditions such as optic neuropathy, 12 13 orbital inflammation, 14 15 ophthalmopathy, 16 and orbital apex syndrome.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Another study by Venkat et al reported a woman who had inflammatory superior limbic keratitis and subsequent bilateral posterior uveitis. 18 Fang et al also reported 3 cases of unspecified “eye inflammation” and 1 case of “uveitis”. 4 In our case, however, anterior segment inflammation was found in both eyes of the patient.…”
Section: Discussionmentioning
confidence: 99%